THE ROLE OF TECHNOLOGY TO SOLVE LANGUAGE LEARNING PROBLEMS: A PRACTICAL CASE OF COMMON CORE SCIENTIFIC STUDENTS - Fakhr-Eddine, I.; Aitdaoud, Mohammed (Arabi : Journal of Arabic Studies, 2019)
The misspellings are among the most important reasons that distort the Arabic language. It is based on the letters that are added or deleted, the words that separates or connects, the Humazat “الهمزات” that are distinct, or the ones that are on one of the three soft letters. The spelling rules subject has received attention from various linguistic communities and specialized scientific commissions in the Arabic language. There have been numerous and various studies on spelling errors among students at different levels of study in a number of Arab countries. Students of educational institutions in Morocco are no exception to this phenomenon of spelling errors. The aim of our research is to shed the light on the types of spelling mistakes made in the Arabic language, how they are made and why. We used a survey that we analyzed using a statistical program to find out the cause of these mistakes, their intersecting and their frequency. Also, we suggest the establishment of a Learning Management System (LMS) based on the e-learning platform Moodle, to remedy to the problems of misspelling.